MITOS IM3 SEBAGAI SOLUSI KONFLIK IBU DAN ANAK DALAM IKLAN “DEKATKAN JARAK NYATAKAN SILATURAHMI” - Ovanuti, Dinda; Ramdani, Guruh (Departemen Ilmu Komunikasi Universitas Andalas, 2025)
According to Mukromin (2019), advertising refers to activities aimed at introducing goods or services through mass media or other forms of communication, with the purpose of interpreting the quality of a product or service based on consumer needs and desires. The main objective of advertising is to communicate the product being promoted through various media channels. The IM3 advertisement titled